Pengaruh Lapisan Pasir di Bawah Fondasi terhadap Redaman dan Frekuensi Natural Akibat Beban Gempa - As’at Pujianto (Universitas Muhammadiyah Yogyakarta, 2009)
Sand layer under foundation has been widely used for vibration damping by an earthquake since centuries ago. Due to being located in earthquake-zone and sand as natural material is widely distributed over regions, research on the use of sand for earthquake vibration damping is becoming important in Indonesia. The aim of this work is to study sand layer behavior in reducing earthquake vibration. Parameters of soil structure, i.e. damping ratio, displacement, soil pressure, and the change of natural frequencydue to the existence of sand layer under foundation were observed. In this study, soil structure was modeled as layered soil profile where top layer is a clay soil layer. Foundation base is located at a depth of 300 cm underlying varied thicknesses of course sand layer, i.e. 0, 50, 100, 150 and 200 cm under foundation. In order to produce various soil pressures, load magnitudes of 0, 10,000, 20,000, 30,000 and 40,000 tons were selected. Therefore, earthquake loadings with high and low frequency from Koyna and Bucharest earthquake record were implemented to soil structure models. Results showed that the increase of sand layer thickness does not essentially affect to the decrease of displacement. It is depending on the frequency of an earthquake. However, a thickness of 50 cm shows decrease of displacement due to high and low frequency earthwuake loading with the average deviation of 3.67 %. The displacement due to Bucharest earthquake loading is greater than that of Koyna earthquake, with the average ratio of 9.38 times. If ground frequency is higher than earthquake frequency, ground displacement is becoming smaller.